2018
DOI: 10.1016/j.biomaterials.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer nanofiber-enabled engineering of biomimetic periosteum for bone repair and reconstruction

Abstract: Periosteum plays an indispensable role in bone repair and reconstruction. To recapitulate the remarkable regenerative capacity of periosteum, a biomimetic tissue-engineered periosteum (TEP) was constructed via layer-by-layer bottom-up strategy utilizing polycaprolactone (PCL), collagen, and nano-hydroxyapatite composite nanofiber sheets seeded with bone marrow stromal cells (BMSCs). When combined with a structural bone allograft to repair a 4 mm segmental bone defect created in the mouse femur, TEP restored do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 42 publications
2
79
0
Order By: Relevance
“…Some studies also revealed the applicability of BM-MSCs-and AD-MSCs-loaded nanofibrous scaffolds in promoting angiogenesis [206][207][208][209]. With the rise of novel cell technologies, such as the methods to manipulate induced-pluripotent stem cells (iPSCs), researchers are currently able to generate iPSC-derived endothelial cells (iPSC-ECs) as a promising source of ECs for therapeutic angiogenesis [210][211][212].…”
Section: Cell-laden Nanofibers For Pro-angiogenesis Strategiesmentioning
confidence: 99%
“…Some studies also revealed the applicability of BM-MSCs-and AD-MSCs-loaded nanofibrous scaffolds in promoting angiogenesis [206][207][208][209]. With the rise of novel cell technologies, such as the methods to manipulate induced-pluripotent stem cells (iPSCs), researchers are currently able to generate iPSC-derived endothelial cells (iPSC-ECs) as a promising source of ECs for therapeutic angiogenesis [210][211][212].…”
Section: Cell-laden Nanofibers For Pro-angiogenesis Strategiesmentioning
confidence: 99%
“…[ 11,23,24 ] Natural polymers are attractive materials for biomedical applications, as they inherently present chemistries similar to the ECM, and they may have the capability to increase cell migration and proliferation. [ 4,22,25,26 ]…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of tissue engineering technology, artificial bone replacement materials have become the main research and development direction of reconstructing the defect bone morphology and function, and have made a lot of achievements [ 105 , 106 ]. Compared with "gold standard" autogenous bone, the advantages of artificial bone replacement materials mainly include the unlimited amount of synthesis [ 107 ], the ability to act as drug delivery carrier [ 108 ], and the ease of functional modification [ 109 ]. Thus, giving the materials new functions such as vascularization [ 110 ], bone targeted recognition [ 111 ], and recruitment of stem cells [ 112 ], are more conducive than the physiological repair of defects.…”
Section: The Destination Of Bp Tissue Engineering Application-bone Thmentioning
confidence: 99%